Managing the embodied carbon of precast concrete columns - Wu, Peng; Sui Pheng, L. (American Society of Civil Engineers (ASCE), 2011)
With the rising recognition of global climate change, the term CO2 emissions is now part of everyday language. The construction industry plays a significant role in economic growth both directly through its activities and indirectly through the provision of buildings and infrastructures for the smooth functioning of businesses. However, this industry is now highly challenged for its detrimental effect on carbon neutral by consuming materials and energy. Research has been conducted to estimate the embodied carbon of construction materials around the world, such as cement, aggregates, aluminum, and steel. These research findings provided fundamental support in estimating the embodied carbon of precast concrete products. This study investigates the production cycle and estimates the embodied carbon of precast concrete columns, which are typically adopted in the Singapore construction industry, where there is a large demand in public housing projects. The results indicate that 609.59 kg of CO2 is emitted in the production cycle of a specific type of precast concrete column. Knowing the embodied carbon of precast concrete columns, regulatory bodies are able to provide further recommendations toward sustainable construction. Research institutes can also benefit from this study to conduct further estimation of embodied carbon of other precast concrete products and finally complete the carbon inventory for the construction industry.